Avaliação do desempenho de um equipamento para medição da susceptibilidade à fragilização por hidrogênio pelo método RSL - Rezende Júnior, Marcus Vinícius (2018)
This study aimed to evaluate the metrological performance of an equipment to characterize the susceptibility of materials to hydrogen embrittlement using the rising step load method. This equipment was verified in two configurations, the first one with a load cell of 20 kN used for specimens with nominal dimensions of 30 mm x 30 mm x 200 mm and the second one with a 1 kN load cell used for test specimens with nominal dimensions of 10 mm x 10 mm x 60 mm. Different metrological parameters were estimated in both configurations: bias, accuracy, expanded uncertainty, repeatability, hysteresis and linearity. Moreover, the effect of the specimen cross-section, notch radius and specimen hardness on the determination of the PFFS (Point of Fast Fracture Strength) value and the susceptibility to hydrogen embrittlement using a full factorial design 2¹ x 2¹ x 3¹ was determined. The gage repeatability and reproducibility (GR&r) of the equipment resulted in a % GR&r value of 6.17 %, indicating that the equipment is an acceptable measurement system. The evaluation of the two equipment configurations showed that the load cells of 20 kN and 1 kN used to measure the force had excellent metrological properties, both in loading and unloading phase. The analysis of variance results considering the three investigated factors showed that only the cross-section factor has statistically significant effect in determining the PFFS value of AISI 4140 steel under the present test conditions. Further analyses of variance, performed separately for each cross section nominal value, showed that for specimens with nominal dimensions of 10 mm x 10 mm x 60 mm, the notch radius and the hardness of the specimen caused statistically significant effects on the determination of the PFFS value.